The importance of historic interior scheme in promoting heritage museum building: case study of Stadthuys Museum building / Norashikin Abdul Karim ... [et al.] - Abdul Karim, Norashikin; Harun, Siti Norlizaiha; Ayob, Salwa; Anuar, Izzat (2022)
Malaysia has taken wise steps to safeguard heritage building assets by making heritage buildings into heritage museum. This effort shows that Malaysia is looking at the importance of heritage buildings as a way of bringing this historic asset into a medium of continuous historical learning. However, to what extent its interior space can be explored and can be a medium for promoting historic interior schemes. The Stadthuys museum can be promoted through its interior appearances. The Stadthuys museum is a heritage Dutch building that still remains intact although it has gone through several phases of the era; English, Dutch, British and Japanese, even its interior space functions have still been recognised even after being converted into a museum. This museum building promotes the Dutch's office interior with the Dutch's bakery house and Dutch Governor's residence. Four essential components that need to be focused by heritage museums are preserving the building interior history, preserving the authenticity of the historic interior scheme of building, preserving the initial space function, and preserving the historic interior features of space. This paper aims to raise awareness among museum's bodies about the importance of the value of historic interior features in future where the exploring needs to be enhanced. Observation on-site, measured drawings, documents study and site tour, were some of the approaches that have been applied to obtain the data. The historic photograph, sketches, drawings, books, and journals were applied to investigate the origin of the building interior space. The results strengthened that the roles of heritage museum buildings are required not only to display and interpret historical object but also to display and communicate the significance of the historic interior features. In other sense, the interior physical of museum buildings can be a priority when planning heritage museum exhibitions in the future.